Optimisation of Signal-controlled Intersection Capacity - Županović, Dino; Anžek, Mario; Kos, Goran (Promet - Traffic&Transportation, 2012)
Road traffic safety is a complex system which combines movement of entities in precisely determined space and time dimension. Each of the entities, with their different properties, sets different requirements to road traffic system, including also other entities. Due to the large number of entities and their characteristic requirements, their interaction results in extremely complex relations which determine the behaviour of the road traffic system. The entities are combined according to their common features into certain groups, the movements of which usually result in conflicts. In such situations it is necessary to ensure the movement of a group of entities. This method of insurance necessarily creates negative consequences for all the entities that participate in road traffic system. In order to mitigate as much as possible these consequences, it is necessary to find an adequate method of optimising road traffic system according to a given criterion. The paper uses the results of the analysis of more than 100 road traffic system models and presents the methodology of determining the level of their interconnection. The level of influence of the basic traffic values on the final effect, i.e. the possibility of optimising signal-controlled intersections has been found and described. KEYWORDS: traffic flow, signalized intersection, pretimedsystem, optimization, 2-phase system, 4-phase system, volume-to-capacity, lost time